2017
DOI: 10.1063/1.5001733
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting-diode Lambertian light sources as low-radiant-flux standards applicable to quantitative luminescence-intensity imaging

Abstract: Planar-type Lambertian light-emitting diodes (LEDs) with a circular aperture of several tens of μm to a few mm in diameter were developed for use as radiant-flux standard light sources, which have been in strong demand for applications such as quantitative or absolute intensity measurements of weak luminescence from solid-state materials and devices. Via pulse-width modulation, time-averaged emission intensity of the LED devices was controlled linearly to cover a wide dynamic range of about nine orders of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In addition, many other inspiring research studies have suggested that EL imaging or mapping is a promising tool for characterizing defect distribution, series resistance distribution, open‐circuit voltage, and minority carrier diffusion length of solar cells. Moreover, compared with the relative EL measurement which could not provide directly absolute information—such as the EL intensity distribution and internal voltage distribution—the absolute EL imaging technique with calibration is an excellent technique for the electrical analyses of solar cells. Numerical simulations are important and useful for the testing of the viability of the proposed physical explanations and can be proven helpful for the in‐depth understanding of experimental EL data.…”
Section: Introductionmentioning
confidence: 60%
“…In addition, many other inspiring research studies have suggested that EL imaging or mapping is a promising tool for characterizing defect distribution, series resistance distribution, open‐circuit voltage, and minority carrier diffusion length of solar cells. Moreover, compared with the relative EL measurement which could not provide directly absolute information—such as the EL intensity distribution and internal voltage distribution—the absolute EL imaging technique with calibration is an excellent technique for the electrical analyses of solar cells. Numerical simulations are important and useful for the testing of the viability of the proposed physical explanations and can be proven helpful for the in‐depth understanding of experimental EL data.…”
Section: Introductionmentioning
confidence: 60%
“…It is rewarding that suspended two-dimensional materials can produce periodic oscillation in the reflection and PL spectra, therefore providing a direct way to fabricate periodic EL devices. 111 Recently, a transient-mode EL device was been fabricated based on WS 2 -metal contact; a centimeter-scale (≈0.5 cm 2 ) visible (640 nm) display was demonstrated, which showcases the potential of TMDC systems for display applications. 112 …”
Section: Novel Led Devicesmentioning
confidence: 99%
“…Previously, we had established a rapid direct detection system for IHC using an antibody-fused BL probe, demonstrating the potential to detect tumor antigens with high sensitivity in routine immune histological examinations [5]. Furthermore, we established a reference LED light source that was characteristic of total flux and light distribution, then calibrated the bioluminescence imaging (BLI) system as an absolute light signal [6]. Using this LED, time-averaged emission intensity could be controlled linearly to cover a wide dynamic range of about four orders of magnitude for several years.…”
Section: Introductionmentioning
confidence: 99%